THE OBJECT MWC 137 - Kondratyeva, L. N. (Одеські астрономічні публікації, 2007)
The main results of the long-term spectral observations of MWC 137 are presented. Variability of the profiles and equivalent widths of Hα, Hβ and HeI, 5876 is shown and discussed.